Modelos Matemáticos e Computacionais no Manejo Integrado de Pragas - Angelocci, Lucas Verdi [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This work was done with the motivation to better carry out effective control of the pest Diaphorina citri, through the use of Integrated Pest Management (IPM), method employing various techniques of pest control with the intent to keep the pest population below a level that causes economic injury to the producer. Combining the use of insecticides with the natural predator of the pest, the Tamarixia radiata, were performed simulations that show how populations of the species evolve in time and space. A mathematical modeling of the population dynamics of the species was realized. From this model, we studied the equilibrium points and its stability. Then, the effect of variation of some parameters in populations were analyzed by observation of simulations or analytically. Spatial configuration was added to the problem by using the formalism of coupled map lattice, allowing the involved species to diffuse across the field. Again, a study of sensitivity to some parameters related to the movement of species was performed. At the end of the project, a wide range of parameters was studied, and predictions were made for the effect on populations of changing parameters such as control threshold, natural biological parameters of the pest and predator, initial populations, predator numbers added to the system in the application of IPM, speed of diffusion of species through the field, monitoring interval and insecticide application, among others. It is hoped that with these predictions and other studies, the orange growers may be helped in the best way to combat this pest

Este trabalho foi realizado com a motivação de estudar o controle da praga Diaphorina citri, através do uso do Manejo Integrado de Pragas (MIP), método que emprega diversas técnicas de controle de pragas com a intenção de manter a população desta abaixo de um nível que cause dano econômico ao produtor. Aliando o uso de inseticidas ao parasitoide natural da praga, a Tamarixia radiata, realizaram-se simulações que mostram padrões espaço-temporais das populações das espécies envolvidas. Para isso, uma modelagem matemática da dinâmica populacional das espécies foi realizada. Foram estudados os pontos de equílibro e a estabilidade destes. Depois, o efeito da variação de alguns parâmetros nas populações foram analisados, seja por observação das simulações ou de forma analítica. Acrescentou-se configuração espacial ao problema, atraves do uso do formalismo de Mapas Acoplados, permitindo que as espécies envolvidas se difundam pelo campo. Novamente um estudo da sensibilidade à alguns parâmetros, relacionados à movimentação das espécies, foi realizado. Ao final do projeto, uma grande gama de parâmetros foi estudada, sendo previsto o efeito nas populações da alteração de parâmetros como Nível de Controle, parâmetros biológicos naturais da praga ou parasitoide, populações iniciais, número de parasitoides acrescentados no sistema na aplicação do MIP, velocidade de difusão das espécies pelo campo, intervalos de monitoramento e aplicação de inseticida, entre outros. Espera-se que com estas previsões e outros estudos, os produtores de laranja possam ser auxiliados na melhor maneira de combater esta praga
Keywords: Pragas - Controle biologico; Inseto - Controle; Modelos matematicos; insetos; Mathematical models; Insects Identification